Maximizing yield of mustard through zinc and boron fertilization - Jha, Shivanand; Anwar, Md Parvez; Rashid, Md Harun; Paul, Swapan Kumar (Fundamental and Applied Agriculture, 2023)
A field experiment was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh, during November 2021 to January 2022 to evaluate the varietal response of mustard to zinc (Zn) and boron (B) fertilization. The experiment comprised two varieties viz., BARI Sharisa-14 and Binasharisa-11, and nine doses of Zn & B viz., Zn 0 kg ha−1 + B0 kg ha−1 (control), Zn2 kkg ha−1, Zn4 kg ha−1, B2 kg ha−1, B4 kg ha−1, Zn2 kg ha−1 +B2 kg ha−1, Zn2 kg ha−1 +B4 kg ha−1, Zn4 kg ha−1 +B2 kg ha−1 and Zn4 kg ha−1 +B4 kg ha−1. The experiment was laid out ina randomized complete block design with three replications. Binasharisa-11 produced taller plants (115.09 cm), the highest number of branches plant−1 (7.85), 1000-seed weight (3.81 g), seed yield (1.76 t ha−1) and stover yield (4.02 t ha−1) while BARI Sharisa-14 gave the lowest values of all parameters. Application of Zn 2 kg ha−1 + B 2 kg ha−1 produced the highest number of branches plant−1 (8.82), total number of siliqua plant−1 (59.11), 1000-seed weight (4.29 g), seed yield (1.84 t ha−1) and stover yield (4.23 t ha−1) and lowest values were found in control. In case of interaction the highest number of branches plant−1 (9.62), effective siliqua plant−1 (54.08), number of seeds siliqua−1 (31.55), seed yield (2.0 t ha−1) and stover yield (4.51 t ha−1) were found in Binasharisa-11 fertilized with Zn 2 kg ha−1 + B 2 kg ha−1 while the lowest values were recorded in BARI Sharisa-14 at control fertilization of Zn & B. Therefore, Binasharisa-11 fertilized with Zn 2 kg ha−1 + B 2 kg ha−1 appears as the promising technique in terms of higher seed yield of mustard. However, further trials can be conducted at different agro-ecological zones of the country to confirm this result.